Georgian Scholar Grigol Peradze - Student of the University of Berlin - Steffi Chotiwary-Jünger, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
Grigol Peradze(1899-1942) conducted important Kartvelological work in Germany, England, France, and Poland. Grigol Peradze was a clergyman. Consequently, his scientific work mainly focused on researching Georgian Medieval Christian literature and introducing it into European scholarly circles of humanities. Grigol Peradze was strongly against the Nazi regime. He died a martyr’s death at Nazi concentration camp and is canonized by the Georgian church. This article represents a study of the period of Peradze’s life when he studied at the University of Berlin. The research is based on the materials of archives. For more archival sources about the life and work ofGrigol Peradzein this period, see the publication in German: Steffi Chotiwari-Junger, Die eine Welt-Grigol Peradzein Berlin and Potsdam vom 4. Jannuar 1922 bis (8.) 29. April 1925: Georgica, 33, 2010, p. 9-36.